Effects Of Land Use On The Nature And Population Of Microorganisms In The Semi-Arid Region Of North-Eastern Nigeria - Bello, HS; Isa, T; Isa, MA; Akinmuisere, K (International Journal of Environment, 2013)
This study was aim to investigate the effects of land use on the nature and population of microorganisms in soil from five different farms within University of Maiduguri, Borno State. A total of ten composite samples were obtained and analyzed in the laboratory. The total microbial population was consistently higher in the grazing reserved land with mean of 105x104CFU/g than in cultivated farms with means of 84.5x104CFU/g, 66x104CFU/g and 66x104CFU/g, for cereal (sorghum), beans and tomato farms respectively. The site with the least microbial population was gum-Arabic plantation with the mean of 29x104CFU/g. Bacteria were the most dominant species at all sites regardless of depths. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 224-230 DOI: http://dx.doi.org/10.3126/ije.v2i1.9223